The Influence of Family Ownership on Long-Lived Asset Write-Offs. (December 2015) - Greco, Giulio; Ferramosca, Silvia; Allegrini, Marco
Building on agency theory, this article investigates whether family firms' accounting behavior regarding long-lived asset write-offs differs from that of nonfamily firms. We provide evidence that nonfamily firms use write-offs for earnings management purposes, while family firms report write-offs coherent with the firm performance. Family firms experience dwindling sales and lower profitability in the years following the write-offs, consistently with an effective decline in their assets value. The findings are consistent with reduced owner-manager agency conflicts in family firms. We find no indication of family entrenchment, which is consistent with family owners being concerned with the reputational damage associated with a loss of a firm's asset value.